Cooperative firms and the crisis: evidence from some Italian mixed oligopolies - Flavio Delbono; Carlo Reggiani (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2013)
We investigate how cooperative firms reacted to the current crisis. This allows us to compare the behavior of cooperative and conventional firms facing exogenous shifts in demand. After a short survey of a stream of theoretical literature, we analyze a large group of Italian production cooperatives in the periods 2003-2010 and 1994-2011 and we contrast co-ops behavior with the overall trend in the industries in which they operate. Our sample's evidence suggests that the cooperative's behavior has a stabilizing effect on employment with respect to shocks in output demand. Unlike profit-maximizers, cooperative firms seem to be adjusting pay more than employment when facing shocks. Production co-ops look better equipped than their profit-maximizing counterparts in tackling the long recession also because they have been very cautious in their profit policies over time. Unlike conventional firms, they have significantly increased their own equity during "good" years instead of distributing large dividends to their members.
Keywords: P13; L13; E32; 330